AZAS PENCEMAR MEMBAYAR SEBAGAI TANGGUNG JAWAB MUTLAK DALAM UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Ratna Mulya Madurani (VERITAS, 2018)
In the framework of Utilitarianism (Utilitarianism) the criteria for determining thegood of a deed is the greatest happiness of the greatest number, the greatesthappiness of the greatest number of people. Utilitarian Theory provides a moralbasis for our responsibility to preserve the environment. According toutilitarianism, an act (or rule) is good, when it brings the greatest pleasure to thegreatest number of people or in other words if it maximizes the benefits. It is clearthat environmental conservation brings the most favorable conditions for allmankind, including future generations.